2007
DOI: 10.1086/511422
|View full text |Cite
|
Sign up to set email alerts
|

Update on the Management of Gonorrhea in Adults in the United States

Abstract: Gonorrhea, the second most commonly reported notifiable disease, is an important cause of cervicitis, urethritis, and pelvic inflammatory disease. The selection of appropriate therapy for gonorrhea (i.e., safe, highly effective, single dose, and affordable) is complicated by the ability of Neisseria gonorrhoeae to develop resistance to antimicrobial therapies. This article reviews the key questions and data that informed the 2006 gonorrhea treatment recommendations of the Centers for Disease Control and Preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
113
0
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(120 citation statements)
references
References 135 publications
0
113
0
7
Order By: Relevance
“…[56][57][58][59][60]71,72 This correlates with the pharmacokinetic properties of the individual antimicrobials. Treatment with spectinomycin has poor efficacy at eradicating pharyngeal gonorrhoea.…”
Section: Therapy For Uncomplicated Gonococcal Infection Of the Pharynxmentioning
confidence: 99%
“…[56][57][58][59][60]71,72 This correlates with the pharmacokinetic properties of the individual antimicrobials. Treatment with spectinomycin has poor efficacy at eradicating pharyngeal gonorrhoea.…”
Section: Therapy For Uncomplicated Gonococcal Infection Of the Pharynxmentioning
confidence: 99%
“…Ciprofl oxacin resistance is greatly increased (21.4%) compared to other national studies. These studies initially observed decreased susceptibility 19,21 followed by drug resistance in Manaus 23 27 (47.7%), have detected high levels of resistance to ciprofl oxacin, and thus its use for the treatment of gonorrhea has been discontinued in these locations 4,32,33 . In addition, specimens with a high level of resistance to ciprofl oxacin (MIC>32µg/ml) that also exhibited resistance to chloramphenicol and tetracycline were identifi ed.…”
mentioning
confidence: 99%
“…In corneal melting cases where there is no correct response to treatment and the perforation risk is imminent, or has already been produced, keratoplasty has proven to be the most efficient invasive therapy and could therefore restore the globe in its whole. It could also reduce the risk of endophthalmitis, if it used at an early stage as in our case [9] [10].…”
Section: Discussionmentioning
confidence: 99%